V12. [18F]-FDG-PET imaging of the cerebral orthostatic tremor network during stance. Issue 8 (August 2015) - Schöberl, F.; Xiong, G.; Feil, K.; Bartenstein, P.; Fougere, C. la; Brandt, T.; Jahn, K.; Strupp, M.; Dieterich, M.; Zwergal, A.
<x xml:space="preserve">Abstract</x> Background and aim Primary orthostatic tremor (OT) is a rare neurological disease of unknown pathophysiology characterized by a high frequency tremor mainly of the legs when standing. The aim of the present study was to depict the cerebral tremor network in OT by [18F]-FDG-PET during standing. Methods Ten patients (mean age 58 ± 12 years) with neurophysiologically proven OT (EMG, posturography) and ten age-matched healthy controls were included in the study. All subjects underwent a [18F]-FDG-PET paradigm during real standing (i.e. injection of [18F]-FDG during upright stance, PET scan 30 min p.i.). As a control condition in a second session a PET was acquired after injection of [18F]-FDG in lying position. PET images were processed by SPM8 software and compared between groups and conditions. Results All patients but no control subject showed a characteristic high-frequency peak at 12–16 Hz in posturography. In healthy subjects the regional cerebral glucose metabolism (rCGM) during standing compared to lying was increased in the vermal cerebellum, thalamus and primary motor region. During standing, OT patients had a relatively increased rCGM in the cerebellum (including the dentate nucleus), the ventrointermediate nucleus of the thalamus and the primary and supplementary motor cortex bilaterally in comparison to the control group. A relatively decreased rCGM was found in the mesiofrontal cortical areas in OT patients during standing. Conclusions In the present study a cerebello–thalamo–cortical tremor network is depicted in a group of OT patients using [18F]-FDG-PET during standing. The data strongly reinforce the idea that the ventrointermediate nucleus of the thalamus may be a therapeutic target for deep brain stimulation in OT.